Penerapan Slow Deep Breathing Terhadap Penurunan Tekanan Darah Pada Lansia Dengan Hipertensi Di Puskesmas Ambawang - Mather Mather; HANDOKO KOKO; Ruri Virdiyant (PENA NURSING, 2023)
One of the non-pharmacological therapies that can be used for people with hypertension is complementary therapy as part of a complete treatment system, but these complements include slow deep breathing exercises, acupuncture, physiotherapy, psychotherapy, yoga, mediation, and aromatherapy. Purpose of Writing To identify the results of the Application of Slow deep breathing on Blood Pressure in the Elderly with Hypertension at the Ambawang Health Center in 2023. Overview of the Case: A woman with the initials Mrs. L is 65 years old complaining of frequent headaches. Mrs. L has a history of hypertension 10 years ago. Mrs. L did not experience emotional disturbances. The client complains of discomfort in the head area, dizziness, feeling of spinning, neck pain, and neck feeling tense until the neck feels uncomfortable since 1 week ago. Application Results After being given the implementation of slow deep breathing with hypertension cases it can be said to be successful. Blood pressure decreased on the second day and resolved on the third day. So that it can speed up the patient's recovery.Conclusion  The results of nursing care in hypertensive patients with slow deep breathing obtained an evaluation of the actions of 3 nursing diagnoses resolved.